BASIC TRAINING OF SPECIALISTS IN IT DIRECTION - Andrey I. Volkov; Alla Yu. Ermakova (Статистика и экономика)
The article shows a contradiction in the guidance document on the organization of educational process in higher education and proposes an approach to the resolution of this contradiction. Formed the content of the basic training of IT-specialists of different directions. Proposed structure and content of the course and final qualifying works.